Health Service Utilization and State Costs Among Adults Aging With Early-Acquired Physical Disabilities in Medicaid Managed Care. (December 2019) - Yamaki, Kiyoshi; Wing, Coady; Mitchell, Dale; Owen, Randall; Heller, Tamar
Objective: We evaluated the impact of Medicaid managed care (MMC) on health service use and state costs among adults with early-acquired physical disabilities.Method: Using claims data, we tracked utilization of the emergency department (ED), inpatient admissions, outpatient physician visits, and state expenditures on enrollees who transitioned to MMC ( n = 881). The inverse propensity score weight and a difference-in-differences regression model were used to estimate the impact of MMC using their counterparts who remained in fee-for-service ( n = 1, 552) as the comparison group.Results: MMC reduced ED use by 3.2% points/month ( p < .001). Relative to younger enrollees (age ⩽45 years), MMC reduced inpatient admissions of older enrollees (age ⩾46 years) by 3.3% points/month ( p < .001), and state expenditures by US$839/month ( p < .01).Discussion: MMC could reduce the hospital service use of and state spending on enrollees with early-acquired physical disabilities. This impact may vary depending on the enrollees' age.